Us and Them - Jón Ólafsson (2010)
Verkefnið er lokað Abstract The essay is about how the Icelandic media has covered China and the image the media has portrayed, over three time periods, the early 20th century, the ninetieth decade of the 20th century and the first decade of the 21st century. In the early 20th century the Icelandic media portrays a negative image of China. The Chinese people are portrayed as dark, evil and unintelligent. Ólafsson an Icelandic missionary creates the image through his two books “Mission in China” and “14 years in China”. The image is influence by the religious conviction of Ólafsson and the misunderstanding caused by the cultural difference he experiences. For few decades China is not often portrayed in the Icelandic media. It is not until the nineties that China is portrayed in a clear and distinct image. In the nineties the Icelandic media portrays China as a human rights violator. The country is covered in a very negative way that is caused by the fall of the Soviet Union. The media in the liberal democratic country, Iceland, choose China to fill up the Soviet Unions place, as an enemy of the freedom and democracy. As China becomes more and more economically important the cover in the Icelandic media becomes increasingly more positive. In the 21st century the image of China has taken a complete U-turn. From being a evil human rights violating country to a friendly business partner. The image of China is influence by business interests in the Icelandic society. The image is never the same in these periods and is always influenced by someone. This is the result of the essay in a very short term. Úrdráttur Ritgerðin er um hvernig Íslenskir fjölmiðlar hafa fjallað um Kína og hvernig ímynd þeir hafa birt af Kína, á þremur tímabilum. Í byrjun 20. aldarinnar, 10. áratug 20. aldarinnar og fyrsta áratug 21. aldarinnar. Í byrjun 20. aldarinnar sýna Íslenskir fjölmiðlar mjög neikvæða ímynd af Kína. Kínverjar eru sýndir sem myrk, ill og illa gefin þjóð. Ólafur Ólafsson, Íslenskur trúboði, býr til þessa ímynd með því að ...